2019
DOI: 10.1101/675025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein function prediction in genomes: Critical assessment of coiled-coil predictions based on protein structure data

Abstract: Coiled-coil regions were among the first protein motifs described structurally and theoretically. The beauty and simplicity of the motif gives hope to detecting coiled-coil regions with reasonable accuracy and precision in any protein sequence. Here, we reevaluated the most commonly used coiled-coil prediction tools with respect to the most comprehensive reference data set available, the entire Protein Data Base (PDB), down to each amino acid and its secondary structure. Apart from the thirtyfold difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We found that DMs accumulate in heptad positions critical for the assembly of coiled-coils (in line with the findings published by Mohanasundaram et al 14 ), N-terminal parts of coiled-coils are more abundant in DMs, and mutations mostly affect homooligomeric coiled-coils. Interestingly, in recent analyses some coiled-coil prediction methods showed a rather low accuracy and their result is sometimes contradictory 17,18 , however, based on the agreement of the distribution of variations predicted by different methods, they show balanced performance on our dataset.…”
Section: Discussionmentioning
confidence: 61%
“…We found that DMs accumulate in heptad positions critical for the assembly of coiled-coils (in line with the findings published by Mohanasundaram et al 14 ), N-terminal parts of coiled-coils are more abundant in DMs, and mutations mostly affect homooligomeric coiled-coils. Interestingly, in recent analyses some coiled-coil prediction methods showed a rather low accuracy and their result is sometimes contradictory 17,18 , however, based on the agreement of the distribution of variations predicted by different methods, they show balanced performance on our dataset.…”
Section: Discussionmentioning
confidence: 61%